Lúdico e o desenvolvimento cognitivo na Educacao Infantil - Moreno, Michele Castelo Branco (Brasil, 2024)
This research aims to develop a reflection on the indigence of pedagogical practice through playing in Early Childhood Education, with a focus on playfulness, in a way that promotes the child's learning and intellectual development, using effective strategies that involve games and pranks. From this, the objective of this study was to analyze the literature published in the format of scientific articles between 2015-2023 on cognitive and human development with playing in Early Childhood Education. Methodologically, the study consists of an integrative review of the literature, with a universe of 05 articles that were collected on the CAPES Periodicals Portal. The data were analyzed descriptively using an instrument called 'IR protocol' and subsequently the findings were subjected to the content analysis procedure. As a result, it was It is possible to construct two categories: 1) The contribution of play to teaching and learning in Early Childhood Education; 2) The importance of playing in the child’s development process. The analysis suggests that Early Childhood Education is the first stage of a child's learning, where they have their first contact in the school environment, and consequently with other children, so at this stage play is very important to develop cognitive skills and abilities, through of different languages, providing sensory discoveries, sociocultural interaction, concentration and children's laterality, through gestures, movements, rules and empathy. Finally, it is concluded that educators adopt playful strategies in their daily practices, creating rich and stimulating learning environments that meet children's cognitive, emotional and social needs.